(untitled) (Journal of Forensic Medicine & Toxicology, 2015)
The study is a retrospective analysis of cases of fatal head injury subjected to medicolegal autopsy at the Department of Forensic Medicine, Jawaharlal Nehru Institute of Medical Sciences (JNIMS), Imphal for three years. The purpose of this study is to know the pattern of head injuries amongst the victims of vehicular accidents in Manipur. Only those cases of road traffic accidents where head injury was the cause of death or a major contributing factor towards the death of the victim were included in the study. A total of 484 medico legal autopsies were conducted between 1st April 2010 and 31st March 2013, at the mortuary of JNIMS, Imphal. Out of these, 178 cases were of Road traffic accidents (RTA) which constituted about 36.77%. Male/female ratio was approximately 4.56:1. Maximum numbers were recorded in the age group of 21 - 30 years of age. In the present study, out of 178 RTA cases, fatal head injuries were noted in 112 cases accounting to 62.92% of all deaths due to road traffic accident. Skull fracture was observed in 74.10% and in 25.90% there were no skull fracture. The commonest type of skull fracture was fissure fracture. Most frequent cranial bone to be fractured was the occipital bone and middle cranial fossa was involved in 49.02%. Intracranial haemorrhage was seen in 104 cases (43.42%) and the commonest type was subarachnoid haemorrhage. Brain was found to be injured in 49 cases. Contre-coup brain lesions were observed in 27 cases of all brain injuries.